THE IMPORTANCE OF TAXONOMY ON BASE SCIENCE: THE CASE STUDY OF THE CRUSTACEAN POPULATIONS OF THE MINHO RIVER ESTUARY (NW IBERIAN PENINSULA) - Gomes, Nuno (2021)
Although species identification is a central component on Biological Sciences, misidentifications are quite common generating error cascade effects on other environmental studies, resulting on erroneous population estimates, status, trends, and distribution data. One of the main causes of these errors occurs when dealing with damaged material, immature specimens, sexual dimorphism, intraspecific variation, and species with poor or outdated descriptions. Furthermore, usually there is no material retained as voucher of the specimens studied in scientific collections, hindering confirmation the identified species, in morphoanatomical and genetic scope. Even with this reliance on species identification taxonomy has been in decline for many years. In this study, we present the case study of the crustaceans identified for the Minho River estuary (NW Iberian Peninsula), using a taxonomic approach comparing these results with the biological surveys obtained through various ecology studies performed for 4 decades. A total of 64 species of crustaceans were identified within this study, in which 44 were new records for the Minho River estuary, compared to the 25 species identified on the biological surveys analyzed. Being one of the first studies of this nature in the Minho River, the main objective will be to provide taxonomic support in future projects in this area, contributing to the knowledge of the fauna of Portugal and the Iberian Peninsula.